Object-oriented database management applications in engineering and computer science / Alfons Kemper, Guido Moerkotte - Kemper, Alfons Heinrich (Prentice Hall, 1994)
Provides a comprehensive state-of-the-art exploration of concepts, tools, design methodologies and systems of object-oriented information management for advance applications in such areas as engineering, VLSI design, architecture and science.